Threading a moving needle: The spatial dimensions characterizing US offshore wind policy drivers. (October 2021) - Russell, Aaron; Bingaman, Samantha; Garcia, Hannah-Marie
Abstract: The Atlantic Coast of the United States represents one of the most promising development environments for offshore wind installation in the world due to the convergence of several geographic factors. These include, but are not limited to, population size and density, electricity prices, ocean depth, wind speed, and the dynamics of the region's current energy infrastructures. However, these have not been sufficient to kickstart a mass movement to offshore energy generation despite two decades of affirmative discussions and some entrepreneurial starts. Planned projects now total over 6 GW. Presently, market variables and institutional controls have become more hospitable for development though undertested except in small pilot projects. Socio-cultural concerns including interaction with the fishers, coastal tourism and real estate, Native American Tribes, and environmental and aesthetic factors have been studied, but applicable information remains limited to reliance on comparisons with European offshore wind research, hypothetical analyses, and attention to small pilot projects. This gap as well as a fundamentally differentiated patchwork of state and local stages means that the current research direction will need to be extended through the development of the first utility-scale projects with attention to new case studies as well as new perspectives, framings, and questions. This report outlines important physical and social policy factors of offshore wind development and then explores several case studies. Highlights: Offshore Wind on the United States East coast is spatially complex. Physical, policy and social factors are reviewed with US studies highlighted. Process participation, place, practice and tribal interests are discussed. Cases of demise and success are outlined as well as future projects.